Analysis of Sulfate (SO4) Concentration in Bittern as Raw Material for Magnesium Sulfate (MgSO4) - Uswatun Hasanah; Nike I. Nuzula; Ashari Wicaksono; Makhfud Efendy; Wiwit S. W. Pratiwi (Journal Omni-Akuatika, 2022)
The investigation on traditional salt production had developed in the characterization of Bittern. Bittern is the dense residual liquor with specific gravity ≥ 1.28 gr/cm3 obtained after precipitation and harvesting of NaCl salt from seawater. In this research, the measurment of sulfate in the bittern was carried out. Sulfate is one of the raw materials for MgSO4. The determination of sulfate concentration is using a turbidimetric method according to SNI 6989 20:2009 using a spectrophotometer at a wavelength of 420 nm.  In this process the Sulfate in an acidic environment reacts with barium chloride (BaCl2) to form barium sulfate (BaSO4) crystals. The light absorbed by the barium sulfate suspension is measured with a photometer and the sulfate content is calculated by comparing the readings with the calibration curve. The results of the analysis showed that at 31o Baume the sulfate content is 40.0 g/L, at 32o Baume the sulfate content is 42.6 g/L, at 33o Baume the sulfate content is 42.8 g/L. The sulfate concentration in the bittern showed a linear increase with increasing water concentration. The sulphate content of bittern with 31oBe levels has an average value of 40.028 g/L, at 32oBe levels the average sulphate content is 42.599 g/L and at 33oBe levels it is 42,825 g/L. Keywords: Bittern, Sulfate, oBe